Peningkatan Daya Saing Produk Melalui Pendampingan Sertifikasi Halal Pada UMKM Menyenk Cafe - Novita Sari Hamidaya; Ratih Mukti Azhar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Menyenk Cafe is a micro, small and medium food and beverage business located in Tenggilis Mejoyo Village, Tenggilis Mejoyo District, Surabaya City. The owner of Menyenk Café Umkm still needs assistance to perfect his product. This is done by providing protection standards to safeguard the products sold. Therefore, the UPN "Veteran" East Java Village Development Team is trying to instill an understanding of the importance of legality in maintaining product safety, order and compliance with regulations, as well as enabling economic actors to implement it. Menyenk Café has gone through Halal Certification as a product requirement based on Islamic law. This transfer of knowledge is a process to create MSMEs whose labels are considered halal. Using Halal Certification has several advantages, namely that producers can open up new opportunities to expand market share. Apart from that, it provides quality and safety standards which involve checking and testing products that meet halal standards, so that the use of halal certification can help improve the quality and safety of products offered to consumers. The aim of this activity is to improve products by providing increasingly reliable product protection standards through legality through Halal certification. Apart from providing understanding, the results of this community service also led to the creation of the Halal logo as a means of marketing products that meet consumer needs for cleanliness and quality standards